Dampak Wisata Kuliner Oleh-oleh Khas Yogyakarta terhadap Perekonomian Masyarakat - Edy Rismiyanto; Totok Danangdjojo (Jurnal Maksipreneur, 2015)
Tourism industry that has recently experienced rapid development is culinary field. It is a tourism activity concerning the provision of food and beverage. The present tourists’ trend is to visit a tourism area to find or hunt local foods. Besides, they are not reluctant to pay in high price to enjoy a meal. Culinary tourism of Yogyakarta special souvenirs become DIY tourism power which is able to create great benefit to the society economy. Business of Yogyakarta special souvenirs such as bakpia, geplak, yangko, gudeg, jadah tempe, kipo, etchave potential to develop local society. The objective of this research is to find out the effect of Yogyakarta special souvenirs culinary tourism towards society economy. The data collection technique utilizes convenience sampling method. The research stages consist of: 1) research instrument preparation stage, including literature review, research design arrangement and initial observation; 2) Field data collection stageis performed with observation, survey/questionnaire, interview and other secondary data collections; 3) Data processing and analysis stage consist of :a) data component processing, such as data reduction and presentation and triangulation, b) data verification, such as data validation using triangulation, c) data analysis using quantitative and qualitative descriptive analysis methods 4) report writing stage is the last research stage, in which all research results that have been analyzed are in form of structured writing. The review strategy of problem analysis uses Logical framework analysis and statistical analysis of two mean different hypothesis test. Based on the previous analysis, it has been proven that the promotion of culinary tourism of Yogyakarta special souvenirs has positive effect on society economy in this sector.